Nature of the antigenic complex recognized by T lymphocytes. I. Analysis with an in vitro primary response to soluble protein antigens (The Rockefeller University Press, 1976)
In order to analyze the genetic factors involved in the regulation of macrophage-T-cells interaction we have developed an in vitro primary response to soluble protein antigens in which nonimmune guinea pig T cells can be sensitized and subsequently challenged in tissue culture with antigen-pulsed macrophages. Antigen-specific T-cell activation, as measured by increased DNA synthesis, occurred when syngeneic antigen- pulsed macrophages were used for both initial sensitization and secondary challenge. No T-cell activation occurred when allogeneic antigen-pulsed macrophages were used for secondary challenge of cells primed when syngeneic macrophages. When allogeneic antigen-pulsed macrophages were used in both primary and secondary cultures it was difficult to assess antigen-specific stimulation due to the substantial mixed leukocyte reaction. However, when T cells from F1 animals were primed with parental antigen-pulsed macrophages they responded only to the parental macrophages used for initial sensitization but not to those of the other parent. These results are discussed with respect to T-cell recognition of a complex antigenic determinant which may include I-region gene products.